Kesukubangsaan dan Posisi Orang Cina dalam Masyarakat Majemuk Indonesia - Parsudi Suparlan (Antropologi Indonesia, 2003)
This article will discuss legal and social discrimination against Chinese ethnic group in Indonesia and will show that the ethnic Chinese has been categorized as The Other since Chinese people are believed to have come from foreign country (China) and maintain their identity as different from other Indonesian ethnic groups. The discussion is focused on the essence of Indonesia as a multicultural society based on ethnicities as social force to develop social interactions within social, economy and political structures at the personal, social and state levels.